Synthesis of wide atomically precise graphene nanoribbons from para-oligophenylene based molecular precursor - Abdurakhmanova, Nasiba; Amsharov, Nadja; Stepanow, Sebastian; Jansen, Martin; Kern, Klaus; Amsharov, Konstantin (Carbon, 2014)
The exploration of graphene nanoribbons (GNRs) and understanding of the structure-property relationship requires the synthesis of GNRs with precisely controllable architecture. In this communication we report on bottom-up fabrication of wide armchair GNR from a para-oligophenylene based molecular precursor. The obtained GNR represents the widest rationally synthesized GNR up to now. © 2014 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20